Comparative Study of Standard Smagorinsky Model and Dynamic Smagorinsky Model in Large Eddy Simulation of Turbulent Channel Flow - Mallik, M. S. I.; Hoque, M. A.; Uddin, M. A. (Journal of Scientific Research, 2020)
This paper presents results of comparative study of large eddy simulation (LES) that is applied to a plane turbulent channel flow. The LES is performed by using a finite difference method of second order accuracy in space and a low-storage explicit Runge-Kutta method with third order accuracy in time. In the LES for subgrid-scale (SGS) modelling, Standard Smagorinsky Model (SSM) and Dynamic Smagorinsky Model (DSM) are used. Essential turbulence statistics from the two LES approaches are calculated and compared with those from direct numerical simulation (DNS) data. Comparing the results throughout the calculation domain, it has been found out that SSM performs better than DSM in the turbulent channel flow simulation. Flow structures in the computed flow field by the SSM and DSM are also discussed and compared through the contour plots and iso-surfaces.